2020
DOI: 10.1007/s00213-020-05651-4
|View full text |Cite
|
Sign up to set email alerts
|

The lateral hypothalamus and orexinergic transmission in the paraventricular thalamus promote the attribution of incentive salience to reward-associated cues

Abstract: Rationale: Prior research suggests that inputs from the lateral hypothalamic area (LHA) to the paraventricular nucleus of the thalamus (PVT) contribute to the attribution of incentive salience to Pavlovian-conditioned reward cues. However, a causal role for the LHA in this phenomenon has not been demonstrated. In addition, it is unknown which hypothalamic neurotransmitter or peptide system(s) are involved in mediating incentive salience attribution.Objectives: To examine: 1) the role of the LHA in the prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
0
12
1
Order By: Relevance
“…To further investigate the role of the LH-PVT pathway in incentive learning, we examined the effects of lesioning the LH and blocking orexinergic activity in the PVT. We found that LH lesions block the development of sign-tracking behavior, and administration of OX-1 or OX-2 antagonists into the PVT attenuates the expression of sign-tracking behavior (Haight et al, 2020). Together, these data led us to develop a neural model of sign-tracking (Figure 2); whereby orexinergic transmission from the LH-PVT encodes the incentive value of cues, altering communication in the PVT-NAcSh pathway, and subsequently, dopamine activity, which we know is critical for incentive learning (Flagel et al, 2011b).…”
Section: A Proposed Role For the Lh-pvt-nac Circuit In Incentive Motivational Processesmentioning
confidence: 72%
“…To further investigate the role of the LH-PVT pathway in incentive learning, we examined the effects of lesioning the LH and blocking orexinergic activity in the PVT. We found that LH lesions block the development of sign-tracking behavior, and administration of OX-1 or OX-2 antagonists into the PVT attenuates the expression of sign-tracking behavior (Haight et al, 2020). Together, these data led us to develop a neural model of sign-tracking (Figure 2); whereby orexinergic transmission from the LH-PVT encodes the incentive value of cues, altering communication in the PVT-NAcSh pathway, and subsequently, dopamine activity, which we know is critical for incentive learning (Flagel et al, 2011b).…”
Section: A Proposed Role For the Lh-pvt-nac Circuit In Incentive Motivational Processesmentioning
confidence: 72%
“…Cue-reward association and salience processing are important components of reward seeking behaviors. PVT neurons are activated in response to cues associated with food reward (Choi et al, 2010;Igelstrom et al, 2010), and influence the attribution of incentive values to reward cues (Haight et al, 2015(Haight et al, , 2017(Haight et al, , 2020Campus et al, 2019). Moreover, both the midline thalamic nuclei (MTN) and the NAc receive prefrontal cortex (PFC) inputs that are able to modulate conditioned reward seeking through divergent cue encoding in PFC neurons (Otis et al, 2017).…”
Section: Reward-seeking Behaviorsmentioning
confidence: 99%
“…satiety-induced decreases in cue-driven sucrose intake (Meffre et al 2019). Interestingly, administration of an OXR-2 antagonist, TCS-OX2-29, into this area significantly reduces lever responding for sucrose in hungry rats whereas SB-334867 has little effect (Haight et al 2020;Meffre et al 2019), suggesting that OXR-2 in the thalamic paraventricular nucleus play a role in the incentive motivational value of the food cue specifically. In line with this, knocking down OXR-1 signalling in the thalamic paraventricular nucleus did not affect progressive ratio responding for a food reward, but did attenuate unconditioned hedonic feeding where the need for learning and motivation is minimal (Choi et al 2012), highlighting that orexin receptor subtypes may play a distinct role in cue-induced reward processing.…”
Section: The Role Of Orexins In Cue-driven Eatingrelated Behaviourmentioning
confidence: 99%